2021
DOI: 10.1002/essoar.10509655.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drivers of late Miocene tropical sea surface cooling: a new perspective from the equatorial Indian Ocean

Abstract:  New late Miocene orbital-resolution Mg/Ca sea surface temperature record from the eastern equatorial Indian Ocean spanning 9 to 5 Ma  Tropical cooling is >3°C; new model simulations suggest that a pCO2 decrease from 560 to 300 ppm could account for most of this cooling  Increase in meridional sea surface temperature gradients over the late Miocene more modest than previously suggested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 133 publications
(207 reference statements)
2
4
0
Order By: Relevance
“…They showed that the amount of cooling they saw in the tropical Indian Ocean would be explainable by a decrease in CO 2 (Burls et al 2021). The cooling at ODP site 811 roughly fits the model data presented in this article, which suggests SSTs of around 28 °C and a cooling of about 2 °C at ODP site 811 (Martinot et al, 2021).…”
Section: Degree and Rate Of Cooling In The Central Indo-pacificsupporting
confidence: 76%
“…They showed that the amount of cooling they saw in the tropical Indian Ocean would be explainable by a decrease in CO 2 (Burls et al 2021). The cooling at ODP site 811 roughly fits the model data presented in this article, which suggests SSTs of around 28 °C and a cooling of about 2 °C at ODP site 811 (Martinot et al, 2021).…”
Section: Degree and Rate Of Cooling In The Central Indo-pacificsupporting
confidence: 76%
“…All data generated for this study (Mg/Ca data, reconstructed SST, and climatic simulations) are archived and publicly available via the PANGAEA data repository online (Martinot et al., 2022a, 2022b). Core‐top Mg/Ca data of Holocene age from ODP Site 758 provided by Gianluca Marino are presented in Table S1 in Supporting Information .…”
Section: Data Availability Statementmentioning
confidence: 99%
“…This intensification could have two origins, an intensification of the wind regime or an increase in deep water formation at high latitudes. The end of the Miocene is marked by a significant global cooling due to a decrease in the CO 2 level and a strengthening of the temperature gradient between the equator and the poles (Herbert et al, 2016;Martinot et al, 2022). The strengthening of this gradient leads to more air mass movement in the atmosphere and thus to an intensification of the Walker and Hadley cells (Kamae et al, 2011).…”
Section: Does the Compilation Provide Support For Any Of The Lmbb Hyp...mentioning
confidence: 99%
“…This event is characterized by high rates of opal accumulation from diatoms and radiolarians and high rates of calcite accumulation from calcareous nannofossils and planktonic foraminifera (e.g. Farrell et al, 1995;Dickens & Owen, 1999;Grant & Dickens, 2002;Diester-Haass et al, 2005;Lyle & Baldauf, 2015;Drury et al, 2021;Bolton et al, 2022). The LMBB event, first described by Farrell et al (1995), has been recovered in multiple sites of the world ocean (Figure 1) but its timing is heterogeneous across the sites and its signature in the data record has been identified from a variety of different proxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation